Peran Surau dan Tradisi Ziarah Tarekat Naqsyabandiyah Syekh Arsyad Batuhampar - Agnes Sherly; Nadia` Erli; Nadia Maisya Putri; Muhammad Fikri Ridho Akbar (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2022)
This article presents research on the role of surau in transmitting Islamic scholarship in Indonesia, especially in West Sumatra. Educational activities in surau usually indicate a desire to understand the teachings of Islam in depth by studying Sufism. One part of Sufism is tariqa which means the way to lead to God. The Naqsabandiyah Order is widely followed by the Minangkabau community which has been disseminated by Sheikh Arsyad Batuhampar. He is a murshid who has a relic of written works that are still read by his students, namely the manuscript Min Makkah ila Misr. The manuscript is an adventure story carried out by Sheikh Arsyad as the author in the tradition of pilgrimage in the Middle East. The formulation of the problem in this article is about the role of surau in Batuhampar and why the tradition of pilgrimage of the Naqsabandiyah order to the tomb of Sheikh Arsyad Batuhampar still survives. This research uses historical methods, namely heuristics, by collecting relevant sources such as manuscripts, verification, interpretation, and historiography. The conclusion of research on the text is that Sufis from the Batuhampar region have a tradition of pilgrimage after the pilgrimage from Mecca to Egypt. This pilgrimage was led by Sheikh Arshad to visit the tombs of Muslim saints as a journey of worship and also a scientific journey. The manuscript of Min Makkah ila Misr was written by Sheikh Arshad himself in the late 19th century. Sheikh Arsyad is one of the leading figures of the Naqshbandiyah Order in the Batuhampar region. Sheikh Arsyad continued what had been started by his father, Sheikh Abdurrahman Batuhampar, namely the surau pesantren system in Batuhampar